2013
DOI: 10.1007/s40279-013-0022-4
|View full text |Cite
|
Sign up to set email alerts
|

Skin Conditions of Baseball, Cricket, and Softball Players

Abstract: Each year in the United States over 80 million people participate in bat-and-ball sports, for example baseball and softball. Cricket, the world's second most popular sport, is enjoyed by hundreds of millions of participants in such countries as India, Pakistan, Australia, New Zealand, Bangladesh, South Africa, West Indies, Sri Lanka, United Kingdom, and Zimbabwe. Although any player can develop skin disease as a result of participation in these bat-and-ball sports, competitive team athletes are especially pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 145 publications
(174 reference statements)
0
10
0
2
Order By: Relevance
“…13,27 Sharing equipment increases the risk of HPV infection and warts. 27,43 Age Rare in children aged <5 y 21 ; children aged ≥5 y and adolescents most affected 6,37 ; peak incidence at age 12-16 y 26 Immune status Increased risk in immunocompromised patients 16 Race More common in whites 4,38 Activities Athletics 23 ; occupation (students, manual laborers) 6 ; walking barefoot 24,39 ; communal shower use 23 ; locker room use 23 ; swimming pool use 24 ; bathroom use 26 ; pedicure with improperly sanitized tools 40…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…13,27 Sharing equipment increases the risk of HPV infection and warts. 27,43 Age Rare in children aged <5 y 21 ; children aged ≥5 y and adolescents most affected 6,37 ; peak incidence at age 12-16 y 26 Immune status Increased risk in immunocompromised patients 16 Race More common in whites 4,38 Activities Athletics 23 ; occupation (students, manual laborers) 6 ; walking barefoot 24,39 ; communal shower use 23 ; locker room use 23 ; swimming pool use 24 ; bathroom use 26 ; pedicure with improperly sanitized tools 40…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Close contact with an affected person (family members, classmates, teammates) 5 ; dual-parent homes 38 ; warm, moist environments 5,25 ; sun exposure Season More common in winter months 39 Socioeconomic status High household income 38 ; advanced level of education in household 38 Trauma Contact with rough surfaces, 26,39 ; weight-bearing points most affected 39,41 ; wet, macerated skin 26,39 ; breaks in skin 39 Preexistent wart Autoinoculation 25,42 Hygiene Sharing unwashed shoes, socks, equipment, and other personal items 43,44 ; using nail files and pumice stones used for warts on other areas of skin 19 ; not changing socks daily 25 ; contact with blood from a wart 14 ; not wearing protective footwear in communal showers and locker rooms; poorly ventilated footwear and athletic clothing; poor personal hygiene Plantar warts present a significant problem to athletes, as the pain can affect the athlete's ability to ambulate. 19 Immunocompromised patients have higher rates of plantar warts, along with increased severity and duration of the lesions.…”
Section: Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Sweating from physical exertion can also cause a greater risk of sunburn and skin damage as sweat increases the photosensitivity of the skin . Popular outdoor sports with extended play intervals such as tennis present a highly significant sun damage and future skin cancer diagnosis risk to players . Research by Jinna and Adams identified that most tennis players reported experiencing at least sunburn, which is not unexpected as tennis is often played out in the open .…”
Section: Introductionmentioning
confidence: 99%
“…Por lo tanto, las verrugas plantares son generalmente diagnosticadas clínicamente (15). En casos de incertidumbre diagnóstica o resistencia al tratamiento, biopsia con histopatología la evaluación puede estar indicada (16).…”
Section: Introductionunclassified